Karyotype Analysis of Tulipa pulchella (Liliaceae) (Fenzl ex Regel) Baker - Kiran, Yasar; Dogan, Gulden; Demirkan, Zeynep (Zafer AKAN [EN], 2016)
Objective:  In this study the somatic chromosome numbers and detailed morphometric properties of Tulipa pulchella (Fenzl ex Regel) Baker was examined. Material and Methods:  The seeds were germinated on moist filter paper in petri dishes at 25°C. Actively growing root tips were pretreated with 0.05 M colchicine for 6 h at room temperature. Then, the root tips were fixed with acetic alcohol (1:3 glacial acetic acid–absolute ethanol) for at least 24 h at 4°C, hydrolyzed in 1 N HCl at 60°C for 1-2 min, then rinsed in tap water for 3–5 min. Finally, they were stained in Feulgen for 1 h and mounted in 45% acetic acid. Digital microphotographs from at least five well-spread metaphase plates were taken using an Olympus BX51 microscope X40 objective and were recorded with an Olympus Camedia C-4000 digital camera. Results:  The chromosome number of Tulipa pulchella is determined as 2n = 24 for this taxon. The karyotype consists of 8 submedian region (sm) and 4 subterminal (st) chromosomes. The metaphase chromosome length ranges from 9.35 to 16.48 ?m, longest to shortest chromosome ratio was 1.9:4.1, total karyotype length (TKL) was 150.99 um and the karyotype symmetry was type 1A. Conclusion: The basic chromosome number of Tulipa pulchella is x=12. The majority of tulip species and cultivars is diploid (2n=2x=24), however, encounters to triploids (2n=3x=36), tetraploids (2n=4x=48) and even some pentaploids (2n=5x=60) and hexaploid (2n=6x=72). Identifying the chromosome number of this species in this study would provide a base for biosystematic studies.